Influence of secondary compound complementarity and species diversity on consumption of Mediterranean shrubs by sheep - Rogosic, Jozo; Estell, Richard E.; Skobic, Dragan; Stanic, Svjetlana (Applied Animal Behaviour Science, 2007)
Generalist herbivores foraging in chemically diverse grazing ecosystems like the Mediterranean maquis increase intake on mixed diets, suggesting they are more able to meet nutritional needs and avoid toxicosis. Thus, our objectives were to determine how shrub species diversity and complementary interactions between tannins and saponins inﬂuence intake of Mediterranean shrubs by sheep. We conducted four experiments (10 days each) comparing intake of mixtures of Mediterranean shrubs varying in number of species and/or principal class of secondary compound (tannins or saponins) by sheep (n = 12). Sheep consumed more total foliage (P < 0.01) when offered a high-tannin shrub (Pistacia lentiscus; Exp. 1), two high-tannin shrubs (P. lentiscus and Arbutus unedo; Exp. 2), or three high-tannin shrubs (P. lentiscus, A. unedo, and Quercus ilex; Exp. 3) when fed in conjunction with a high-saponin shrub (Hedera helix) than with an equal number of high-tannin shrubs (20.9 g/kg BW versus 16.3 g/kg BW; 28.8 g/kg BW versus 20.8 g/kg BW; and 35.3 g/kg BW versus 26.9 g/kg BW). Likewise, sheep ate more foliage (P < 0.01) of each additional individual shrub (P. lentiscus, A. unedo, and Q. ilex) in the mixture when fed with H. helix than with an equal number of high-tannin shrubs (8.2 g/kg BW versus 5.0 g/kg BW; 13.3 g/kg BW versus 10.7 g/kg BW; and 7.6 g/kg BW versus 5.2 g/kg BW; Exps. 1–3, respectively), suggesting a complementary interaction between tannins and saponins may have occurred. Sheep also appeared to increase total shrub intake as number of shrub species on offer increased, regardless of number of classes of compounds present. Our ﬁndings suggest that secondary compounds in Mediterranean shrubs (tannins and saponins) are complementary. Species diversity also plays an important role in diet selection, as plant species with different types and amounts of nutrients and phytotoxins may affect forage intake and animal production. This knowledge will help livestock producers to capitalize on phytochemical interactions to enhance intake, optimize forage utilization, and ultimately improve performance of browsing ruminant herbivores
Keywords: Biodiversity; Complementarity; Mediterranean maquis; Saponins; Secondary compounds; Sheep; Shrubs; Tannins

Influence of secondary compound complementarity and species diversity on consumption of Mediterranean shrubs by sheep - Rogosic, Jozo; Estell, Richard E; Skobic, Dragan; Stanic, Svjetlana (Applied Animal Behaviour Science, 2007)
Generalist herbivores foraging in chemically diverse grazing ecosystems like the Mediterranean maquis increase intake on mixed diets, suggesting they are more able to meet nutritional needs and avoid toxicosis. Thus, our objectives were to determine how shrub species diversity and complementary interactions between tannins and saponins inﬂuence intake of Mediterranean shrubs by sheep. We conducted four experiments (10 days each) comparing intake of mixtures of Mediterranean shrubs varying in number of species and/or principal class of secondary compound (tannins or saponins) by sheep (n = 12). Sheep consumed more total foliage (P < 0.01) when offered a high-tannin shrub (Pistacia lentiscus; Exp. 1), two high-tannin shrubs (P. lentiscus and Arbutus unedo; Exp. 2), or three high-tannin shrubs (P. lentiscus, A. unedo, and Quercus ilex; Exp. 3) when fed in conjunction with a high-saponin shrub (Hedera helix) than with an equal number of high-tannin shrubs (20.9 g/kg BW versus 16.3 g/kg BW; 28.8 g/kg BW versus 20.8 g/kg BW; and 35.3 g/kg BW versus 26.9 g/kg BW). Likewise, sheep ate more foliage (P < 0.01) of each additional individual shrub (P. lentiscus, A. unedo, and Q. ilex) in the mixture when fed with H. helix than with an equal number of high-tannin shrubs (8.2 g/kg BW versus 5.0 g/kg BW; 13.3 g/kg BW versus 10.7 g/kg BW; and 7.6 g/kg BW versus 5.2 g/kg BW; Exps. 1–3, respectively), suggesting a complementary interaction between tannins and saponins may have occurred. Sheep also appeared to increase total shrub intake as number of shrub species on offer increased, regardless of number of classes of compounds present. Our ﬁndings suggest that secondary compounds in Mediterranean shrubs (tannins and saponins) are complementary. Species diversity also plays an important role in diet selection, as plant species with different types and amounts of nutrients and phytotoxins may affect forage intake and animal production. This knowledge will help livestock producers to capitalize on phytochemical interactions to enhance intake, optimize forage utilization, and ultimately improve performance of browsing ruminant herbivores
Keywords: Biodiversity; Complementarity; Mediterranean maquis; Saponins; Secondary compounds; Sheep; Shrubs; Tannins

Role of species diversity and secondary compound complementarity on diet selection of Mediterranean shrubs by goats. - Rogosic, Jozo; Estell, Richard E; Skobic, Dragan; Martinovic, Anita; Maric, Stanislava (Journal of chemical ecology, 2006)
Goats foraging on Mediterranean shrubs containing secondary compounds (toxins) may consume a variety of shrubs that contain different phytotoxins, thereby increasing shrub intake and avoiding toxicosis. We conducted eight experiments to examine whether goats offered different mixtures of shrubs containing different phytotoxins (tannins and saponins) would consume more shrub biomass than goats offered one shrub a single phytotoxin (tannin or saponin). In the first three experiments, goats fed a mixture of three tannin-rich shrubs (Quercus ilex, Arbutus unedo, and Pistacia lentiscus) ate more foliage than goats offered only one shrub (23.2 vs. 10.7 g/kg BW; 25.2 vs. 13.4 g/kg BW, and 27.9 vs. 7.9 g/kg BW), regardless of tannin concentration in individual shrub species. Goats also consumed more foliage when offered the same three tannin-rich shrubs than when offered the saponin-rich shrub Hedera helix (25.4 vs. 8.0 g/kg BW). However, goats offered a mixture of the same three tannin-rich shrubs consumed less foliage than goats offered a mixture of two shrubs containing tannins and saponins: Quercus and Hedera (21.6 vs. 27.1 g/kg BW), Arbutus and Hedera (21.8 vs. 27.1 g/kg BW), and Pistacia and Hedera (19.7 vs. 22.0 g/kg BW). Comparison of intake of shrubs containing only tannins or saponins to intake of shrubs containing both tannins and saponins indicated that goats consumed more total biomass when fed with shrubs with both classes of compounds than with either tannins or saponins alone. Our results suggest that goats can increase intake of Mediterranean shrubs high in secondary compounds by selecting those with different classes of phytotoxins. Simultaneous ingestion of shrubs containing tannins and saponins may promote chemical interactions that inhibit toxic effects of these phytotoxins in the intestinal tract. In addition to complementary interactions between tannins and saponins, biological diversity within Mediterranean maquis vegetation also plays a positive role in increasing shrub intake by goats.
Keywords: Biodiversity; Goats; Maquis; Mediterranean shrubs; Saponins; Secondary compounds; Tannins

Role of species diversity and secondary compound complementarity on diet selection of Mediterranean shrubs by goats. - Rogosic, Jozo; Estell, Richard E.; Skobic, Dragan; Martinovic, Anita; Maric, Stanislava (Journal of chemical ecology, 2006)
Goats foraging on Mediterranean shrubs containing secondary compounds (toxins) may consume a variety of shrubs that contain different phytotoxins, thereby increasing shrub intake and avoiding toxicosis. We conducted eight experiments to examine whether goats offered different mixtures of shrubs containing different phytotoxins (tannins and saponins) would consume more shrub biomass than goats offered one shrub a single phytotoxin (tannin or saponin). In the first three experiments, goats fed a mixture of three tannin-rich shrubs (Quercus ilex, Arbutus unedo, and Pistacia lentiscus) ate more foliage than goats offered only one shrub (23.2 vs. 10.7 g/kg BW; 25.2 vs. 13.4 g/kg BW, and 27.9 vs. 7.9 g/kg BW), regardless of tannin concentration in individual shrub species. Goats also consumed more foliage when offered the same three tannin-rich shrubs than when offered the saponin-rich shrub Hedera helix (25.4 vs. 8.0 g/kg BW). However, goats offered a mixture of the same three tannin-rich shrubs consumed less foliage than goats offered a mixture of two shrubs containing tannins and saponins: Quercus and Hedera (21.6 vs. 27.1 g/kg BW), Arbutus and Hedera (21.8 vs. 27.1 g/kg BW), and Pistacia and Hedera (19.7 vs. 22.0 g/kg BW). Comparison of intake of shrubs containing only tannins or saponins to intake of shrubs containing both tannins and saponins indicated that goats consumed more total biomass when fed with shrubs with both classes of compounds than with either tannins or saponins alone. Our results suggest that goats can increase intake of Mediterranean shrubs high in secondary compounds by selecting those with different classes of phytotoxins. Simultaneous ingestion of shrubs containing tannins and saponins may promote chemical interactions that inhibit toxic effects of these phytotoxins in the intestinal tract. In addition to complementary interactions between tannins and saponins, biological diversity within Mediterranean maquis vegetation also plays a positive role in increasing shrub intake by goats.
The following values have no corresponding Zotero field: accession-num: 16770718
Keywords: Biodiversity; Goats; Maquis; Mediterranean shrubs; Saponins; Secondary compounds; Tannins